Assessment of carbon footprint performance by electric power enterprises in China - Yuan, Peng; Zhang, Yinya; Li, Feng; Chen, Shuangyin (Frontiers in Energy Research, 2023)
Carbon neutrality is transitioning from a global consensus to global action. The power industry must urgently address carbon reduction and establish an effective evaluation system. However, current standard systems and literature studies both domestically and internationally reveal significant issues with the scientific, systematic, and operational aspects of carbon performance index systems.Therefore, this paper proposes the development of a carbon performance evaluation system for electric power enterprises, comprising of two subsystems: carbon management and carbon reduction.The evaluation system takes into full consideration the transmission and distribution characteristics of power grid companies, and conducts an empirical analysis on a regional power grid in China, including four provincial power grid companies A, B, C and D. The findings indicate that the regional Power Grid has been committed to low-carbon initiatives for an extended period of time, with a greater emphasis on carbon reduction performance rather than carbon management performance between 2012 and 2021. To further enhance the potential for carbon reduction, it is imperative to prioritize carbon management in subsequent phases.